2020
DOI: 10.14295/cs.v11i0.3206
|View full text |Cite
|
Sign up to set email alerts
|

Quality of guava fruits bagged with different materials in an organic system

Abstract: This study aimed to evaluate the interference of bagging materials on the incidence of insect larvae and the physical and chemical quality of the guava cv. Paluma in an organic system. The experimental design was in randomized blocks with seven treatments and four replications of 25 fruits each. The bagging materials (treatments) were: nonwoven fabric (TNT), transparent plastic bag, white plastic bag, parchment paper, kraft paper, and non-bagged fruits (control). The titratable acidity (TA), ascorbic acid, sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…In addition, bagging is able to promote the production of high-value organic fruits, as demonstrated for organic peaches in the southeastern United States by Allran et al [15], who showed that fruit quality (size, Brix degree, acidity) was similar between bagged and control fruits, and by Campbell et al [16], who reported that bagging protects against various pests and diseases but has minimal effects on organic peach quality. Similar findings were obtained by Araújo Neto et al [17] after a bagging treatment of organic guava fruits. In addition, for organic fruits, bags can be doubled [18], or, in conventional farming, impregnated with insecticide [19] or sprayed with insecticides/fungicide before bagging [20].…”
Section: The Role Of Bagging On Fruit Qualitysupporting
confidence: 90%
“…In addition, bagging is able to promote the production of high-value organic fruits, as demonstrated for organic peaches in the southeastern United States by Allran et al [15], who showed that fruit quality (size, Brix degree, acidity) was similar between bagged and control fruits, and by Campbell et al [16], who reported that bagging protects against various pests and diseases but has minimal effects on organic peach quality. Similar findings were obtained by Araújo Neto et al [17] after a bagging treatment of organic guava fruits. In addition, for organic fruits, bags can be doubled [18], or, in conventional farming, impregnated with insecticide [19] or sprayed with insecticides/fungicide before bagging [20].…”
Section: The Role Of Bagging On Fruit Qualitysupporting
confidence: 90%
“…Bhagawati et al [20] observed that fruit biochemical properties, total soluble solids, and total sugars increased with improved pruning severity and reported higher TSS, ascorbic acid, total sugar, reducing sugar, and non-reducing sugar contents under more drastic pruning, but much of the productivity and quality of the fruits in the harvests also suffered variations due to the seasonality of the seasons. Araújo Neto et al [32] observed that regardless of the pruning levels, biochemical changes naturally arise due to the genetic characteristics of the cultivar.…”
Section: Characteristicmentioning
confidence: 99%